(untitled) (Research, Society and Development, 2021)
The theme of this work investigates the philosophical principles of The immortality of the soul in Plato. The methodology used was exploratory and bibliographical research on texts from books and effective articles on the subject. They expose hypotheses about the immortal soul, and clarify its importance in philosophical thought. The Platonic conviction is without a doubt the most expressive effect on the traditional essence of man, and up to the present moment, the existing reflections of man in civilization demonstrate continuous Platonic aspects. Studies on Platonic anthropology can be considered in summary, in which the pre-Socratics are based on the coexistence of man with the kósmos, under the sophistic teachings of a being of paideia dedicated to political life, and to the hegemonic spoils of Socrates of the inner man and the psyche. Different researchers consider the Platonic idea of ​​man a step backwards in the direction of studies of society at a time when Sophistic thoughts were essential to distinct and essential creativity of man’s actions, when they seemed to be limited by the tasks, of prototypes of perfection of the theory of Ideas , and the equity of human science, where they are involved by the duality of the somapsyche preserved in the Phaedo. It is essential not to overlook the fact that Platonic ideas had strong factual actions in the rise of philosophy, and in the development of the culture of the European man, in the continuous society.